Identification of differentially expressed genes in early-postmortem Semimembranosus muscle of Italian Large White heavy pigs divergent for glycolytic potential. (May 2022) - Davoli, Roberta; Vegni, Jacopo; Cesarani, Alberto; Dimauro, Corrado; Zappaterra, Martina; Zambonelli, Paolo
Abstract: Glycolytic potential (GP) is one of the postmortem traits used to predict the quality of the final meat products. Despite that, the knowledge of the molecular and metabolic pathways controlling this trait is still not complete. To add some information on this field we used two pools of Italian Large White heavy pigs divergent for GP to investigate through a microarray approach the differences of gene expressions between the two pools. On the whole, 32 genes were differentially expressed, and among them 31 were overexpressed in low GP pool. These genes were involved in mitochondrial functions and adenosine triphosphate (ATP) biosynthetic processes, in calcium homeostasis, and in lipid metabolism, with Peroxisome proliferator-activated receptor (PPAR) signaling being a possible master regulator of the molecular differences observed between the two pools. The different GP levels between the two pools could have determined in low GP muscles a more rapid occurrence of the molecular cascade related to the events triggering cell death. Highlights: Understanding the molecular basis of glycolytic potential is essential. Samples with divergent glycolytic potential had 32 genes differentially expressed. Almost all genes were up-regulated in low glycolytic potential pig muscles. Low glycolytic potential samples showed an up-regulation of PPAR signaling genes. A low glycolytic potential boosted genes related to mitochondrial functionality.